Programming Elixir : functional, concurrent, pragmatic, fun - Thomas, David, 1956- (Pragmatic programmers., 2016)
You want to explore functional programming, but are put off by the academic feel (tell me about monads just one more time). You know you need concurrent applications, but also know these are almost impossible to get right. Meet Elixir, a functional, concurrent language built on the rock-solid Erlang VM. Elixir's pragmatic syntax and built-in support for metaprogramming will make you productive and keep you interested for the long haul. This book is the introduction to Elixir for experienced programmers. Maybe you need something that's closer to Ruby, but with a battle-proven environment that's unrivaled for massive scalability, concurrency, distribution, and fault tolerance. Maybe the time is right for the Next Big Thing. Maybe it's Elixir . This edition of the book has been updated to cover Elixir 1.2, including the new with expression, the exrm release manager, and the removal of deprecated types.